Кто есть кто в истории СССР - Залесский Константин Александрович (Кто есть кто, 2011)
Экземпляры: РБ (02.04.2012) / Инвентарный номер: 46784 / Цена: 183.38 / Сис.шифр: 63.3(2)6 / Авт.знак: З-23 / ББК: 92